Molecular screening of rice genotypes for submergence tolerance - Aryalekshmi, A S (Department of Plant Biotechnology, College of Agriculture, 2018)
Rice (Oryza sativa L.) is the most important staple food crop that providing food to about half of the population. One of the major constraints in rice cultivation worldwide is submergence stress. This mainly affects flood prone areas like kuttanadu Pokkali as well as low lying paddy fields in Kerala. Sub1 is a major quatitative trait locus (QTL) representing a cluster of three ethylene responsive factor (ERF) genes: Sub1A, Sub1B and Sub1C that confers submergence tolerance to rice genotype. Submergence tolerant rice variety is credited with maintaining energy and alcoholic fermentation which require high levels of carbohydrates. Sub1 locus contain Sub1A, Sub1B and Sub1C, all of which are encode ethylene responsive factor and are up regulated under submergence, but only Sub1A is responsible for the flash flood tolerance. The near isogenic lines generated by the introgression of the Sub1 from FR13A into to susceptible cultivar shows restricted shoot elongation similar to FR13A. Submergence tolerant plants suppress the expression of gene encoding α- amylase and sucrose synthase, which are involved in sucrose metabolism. Sub1 A enhance the expression of genes encoding SLENDER RICE -1 (SLR1) and SLR1 like 1(SLRL1), which are key repressor of gibberellins (GA) signalling in rice; it also negatively regulate s the GA response in order to restrict shoot elongation under submergence. Rice varieties with the Sub1 gene were shown higher survival rate with better yield even after 2 weeks of submergence stress. The advancement of marker assisted selection (MAS) have striking impacts on developing improved Sub1 varieties that can meet the increasing demands of consumers along with population hike. In the present study, two rice genotypes were observed with Sub1 QTL using SSR markers through molecular characterization in order to find out the best submergence tolerant lines. Moreover this finding lays the foundation for further researches with sub 1 QTL for crop improvement.